Rebuilding a Social Contract: The Role of Media and Academia in shaping a new narrative in Pakistan: The Role of Media and Academia in shaping a new narrative in Pakistan - Agnieszka Kuszewska, (Ph.D., Dr. Habil.) (The Journal of Humanities & Social Sciences, 2019)
The paper aims to provide an insight into the role of media and academia in shaping a new narrative in Pakistan (by strengthening the national cohesion, economic and social progress), with reference to the fundamental laws as enunciated in the Constitution of the Islamic Republic of Pakistan. The initial research hypothesis envisages the necessity of providing an updated narrative for rebuilding the social contract in order to introduce greater social equality and provide better chances for the multidimensional development of Pakistan’s citizens. There are three major assumptions in this research: There is a need to come up with an updated formula for the state-society relations and need to re-negotiate the social contract at multiple levels by taking into consideration the voice of the public. All decision-makers and influencers from the media, civil society, civil and military bureaucracy, business and academia, have their distinctive role in rebuilding/renewing the social contract. The media and academia have unprecedented role in the development of a rules-based society, thus their contribution to reshaping a narrative in Pakistan should not be underestimated. Modern, 21st century social order should adhere to the principles of equality and empowerment of the underprivileged groups, as articulated in the Constitution of the Islamic Republic of Pakistan.